Patterns of Substrate Bioerosion by Excavating Sponges From the Southwest and Central Pacific Ocean - Pohler, Susanne M. L.; Feussner, Klaus; Kaniki, Henry V.; Rashni, Bindiya; Wendt, Hans (Frontiers in Earth Science, 2022)
Reef rubble from a number of locations in the southwest and central Pacific (Fiji, Kiribati, Solomon Islands) were surveyed for their level of infestation with bioeroding sponges. The assessment was by random sampling of reef rubble in shallow water ranging from intertidal to subtidal down to 15 m of water depth. It was found that essentially four styles of bioerosion prevail. (1) small cavities with roundish crossections comonly produced by Pione spp and Cliona sp. cf. C. macgeachii Holmes. (2) Large cavities in the order of cm-size are for example produced by Aka spp., Cliothosa spp., Cliona sp. cf. C. janitrix Topsent, Cliona sp. cf. C. ensifera Sollas and others. Multiple etchings which can degrade the interior of coral rubble on a scale of a few cm in diameter are typically produced by Cliona ex gr. orientalis Thiele and C. ex gr. celata Grant. Large hadromerid sponges are capable of eroding into solid reef rock and produce silt-, sand- and pebble-sized fragments. Observed was the activity of Spheciospongia solida Ridley & Dendy and S. sp. cf. S. inconstans var. digitata Dendy. The large hadromerid sponges are the most efficient eroders on the reef. Species of Pione are abundant at all sites from intertidal to subtidal and although it is a weak bioeroder it may be the most destructive by number.